A Cartel Analysis of the German Labor Institutions and Its Implications for Labor Market Reforms - Justus Haucap; Uwe Pauly; Christian Wey (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
This paper offers a cartel explanation for the stability of German collective bargaining institutions.We show that a dense net of legal safeguards has been yarned around the wage setting cartel. These measures make deviation by cartel insiders less attractive and simultaneously erect entry barriers for alternative unions. As we argue many recent labor policy measures, which make wages more flexible, serve to further stabilize the labor cartel, while truly pro-competitive proposals have not been implemented exactly because of their destabilizing effects.We propose policy measures that remove entry barriers and facilitate outside competition by alternative collective bargaining organizations.
Keywords: J52; K31; L12; 330; Labor market cartel; labor market institutions; collective bargaining; Tarifpolitik; Lohnverhandlungen; Kartell; Insider-Outsider-Modell; Arbeitsmarktflexibilisierung; Deutschland